Biofeedback in sport and education - Liparoti, M.; Lopez, E. T. (Journal of Human Sport & Exercise, 2021)
Usually, the term training is used to indicate a workout that aims to improve the physical performance of athletes. However, it is important to consider that training does not only affect physical features but also influences several cognitive components, consequently different behavioural expressions. This study aims to collect the main scientific evidence on the role of training based on biofeedback signals. Biofeedback is a technique useful not only for recognizing, evaluating and modulating different physiological responses but also for preventing any alterations and trauma. This work could be very important especially in the sports field, where training based on biofeedback, could be decisive for an improvement in the athlete's performance.